Penentuan Strategi Promosi Digital Klinik Kecantikan Berbasis Retensi Konsumen dengan Metode TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) - Nuridayanti, Nuridayanti; Josua, Dian Pertiwi; Sarifah, Iva; Ahmad, Nurul Qomariyah; Jubaedah, Lilis; Ridwan, Achmad; Rohima , Azizah Aulia (Jurnal Tata Rias, 2024)
This study aims to determine the most effective digital promotion strategy for increasing customer retention at Beauty Clinics. Five main criteria are set as the basis for assessment, namely engagement rate, content relevance, platform reach, customer feedback responsiveness, and conversion rate. This study involved five alternative digital promotion strategies: (1) interactive social media campaign, (2) digital loyalty program, (3) collaboration with influencers, (4) segmented paid advertising, and (5) SEO and website optimization. The assessment was conducted by five experts in the fields of digital marketing and beauty clinic management, utilizing a 4-point Likert scale. TOPSIS analysis was conducted through the stages of decision matrix normalization, weighting, determining positive and negative ideal solutions, and calculating Euclidean distance and preference values (Closeness Coefficient). The results showed that the interactive social media campaign strategy obtained the highest Closeness Coefficient value of 0.812, followed by the digital loyalty program (0.748) and collaboration with influencers (0.691). Meanwhile, the SEO website optimization strategy obtained the lowest value (0.581). These results indicate that a direct social interaction-based promotional approach is more effective in increasing customer loyalty in the service sector.